Understanding Arctic Ocean Processes Under Changing Ice Cover. Issue 35 (2nd September 2014) - Polyakov, Igor; Padman, Laurence; Hutchings, Jennifer
<x xml:space="preserve">Abstract</x> As Arctic sea ice declines, heat transport into and through the upper ocean plays an increasing role in the highly coupled atmosphere‐ice‐ocean system. The processes by which the ocean affects sea ice are, however, poorly understood. Understanding processes controlling delivery, storage, and release of heat by the Arctic Ocean is an urgent task.